BUDAYA HUKUM DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Arthani, Ni Luh Gede Yogi (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
AbstractCorruption is seen as a serious crime because it has eliminated the economic and social rights of the people. People really hate corruption, they even condemn the criminals who have stolen state funds. On the other hand, people have the habit of giving bribes to get what they want, such as to become civil servants, speeding up the processing of documents and others. This study examines the policy of combating corruption and perceptions of corruption.Indonesiaâs anti-corruption policy rests on three elements in the legal system, namely the legal substance, legal structure and legal culture. Indonesia had the rule of law and law enforcement are adequate to combat corruption, but the problem lies in the commitment in law enforcement. The legal culture of society have an important role in the prevention of corruption. Community on the one hand the fight against corruption, but on the other hand it supports corruption. Bribery done to facilitate their getting his wish.